Language amotivation and approaches to learning English among Filipino college freshmen - Lucas, Rochelle Irene G. (Animo Repository, 2008)
The present study explores Filipino college freshmen students' approaches to learning in relation to amotivation (possible lack of motivation in learning English as a second language) and related experiences in using English outside the language classroom. Adapting Biggs (2001) and Legault et al's (2006) to evaluate the learning approaches of the students in studying the target language, the researchers surveyed 224 students from different colleges in the university taking the first General Education English course (English one). The results of the study indicate that university freshmen students are neither predominant on either deep approach nor surface approaches to learning. They use both strategies to almost the same extent. In terms of the dimensions of amotivation, the results indicated that freshmen students did not exhibit much of the indicators of amotivation implying that they still show interest and are motivated to learn english as a second language. The cohesiveness of their responses to questions on amotivation also indicated that they have more or less the same perceptions of the value of the task, task characteristics, and their beliefs about their abilities and efforts in learning english.